Impacted cisterna magna without syringomyelia associated with lancinating headache, throbbed nuchal pain and paraparesis treated byposterior fossa decompression Cisterna magna impactada sem siringomielia associada a cefaléia lancinante, dor na nuca terebrante e paraparesia tratadas com descompressão da fossa posterior - José Alberto Gonçalves da Silva; Maria do Desterro Leiros da Costa; Luiz Ricardo Santiago Melo; Antônio Fernandes de Araújo; Everardo Bandeira de Almeida (Arquivos de Neuro-Psiquiatria)
A 29-year-old woman with acute lancinating headache, throbbed nuchal pain and subacute paraparesis underwent brain MRI in supine position that depicted: the absence of the cisterna magna, filled by non herniated cerebellar tonsils and compression of the brain stem and cisternae of the posterior fossa, which are aspects of the impacted cisterna magna without syringomyelia and without hydrocephalus. During eight days, pain was constant and resistant to drug treatment. Osteodural-neural decompression of the posterior fossa, performed with the patient in sitting position, revealed: compression of the brainstem, fourth ventricle and foramen of Magendie by herniated cerebellar tonsils, which were aspirated. Immediately after surgery, the headache and nuchal pain remmited. MRI depicted the large created cisterna magna and also that the cerebellar tonsils did not compress the fourth ventricle, the foramen of Magendie and the brainstem, besides the enlargement of posterior fossa cisternae. Four months after surgery, headache, nuchal pain and paraparesis had disappeared but hyperactive patellar and Achilles reflexes remained. Uma paciente de 29 anos de idade com quadro agudo de cefaléia lancinante, dor terebrante na nuca e paraparesia subaguda foi submetida a RM do encéfalo, em posição supina, que revelou: ausência da cisterna magna, preenchida por tonsilas cerebelares não herniadas e compressão do tronco encefálico e das cisternas da fossa posterior, compatíveis com o diagnóstico de cisterna magna impactada sem siringomielia e sem hidrocefalia. Por oito dias a dor foi constante e resistente aos analgésicos. Com a paciente em posição sentada, foi realizada descompressão osteodural-neural da fossa posterior associada a aspiração das tonsilas cerebelares. Os achados perioperatórios foram caracterizados por herniação das tonsilas cerebelares que comprimiam o tronco cerebral, o quarto ventrículo e o forame de Magendie. No pós-operatório imediato houve remissão da cefaléia e da dor na nuca. A RM evidenciou a cisterna magna recém-criada, alargamento do quarto ventrículo e das cisternas do tronco encefálico. Quatro meses depois, a paciente continuava sem cefaléia, sem dor na nuca e sem paraparesia. Entretanto, permaneceu a hiperatividade dos reflexos patelares e aquileus.